2013
DOI: 10.1017/s0022377813000469
|View full text |Cite
|
Sign up to set email alerts
|

The quantum plasma lens concept: A preliminary investigation

Abstract: Recently, a theoretical investigation of the collective and nonlocal quantum effects has been carried out within the framework of a quantum approach to the relativistic charged particle beam travelling in a cold, collisionless, strongly magnetized plasma. This has been done taking into account both the plasma wake field excitation and the quantum paraxial approximation. On the basis of this theory, here we carry out a preliminary study of the transverse effects experienced by a cold relativistic beam through a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Such model successfully described the beam's selffocusing and self-pinching equilibria, when the spot size of the beam was larger and smaller than the wavelength of the wake field, respectively. More recently, this approach has been extended to the case of self consistent PWF excitation in a cold magnetised plasma for both long nonlaminar warm relativistic driving beam (quantum-like domain of TWM) [3,4] and relatively cold relativistic quantum driving beam (quantum domain) [5,6]. Similarly, the self-modulation of a relativistic charged-particle beam as thermal matter wave envelope and the possibility of its destabilization was studied in [7] using the quantum-like description provided by the TWM in which the beam dynamics is governed by a Zakharov-type system of equations, comprising a Poissonlike equation for the wake potential and a nonlinear Schrödinger equation governing the spatiotemporal evolution of the thermal matter wave envelope, whose dispersion coefficient is proportional to the beam thermal emittance.…”
mentioning
confidence: 99%
“…Such model successfully described the beam's selffocusing and self-pinching equilibria, when the spot size of the beam was larger and smaller than the wavelength of the wake field, respectively. More recently, this approach has been extended to the case of self consistent PWF excitation in a cold magnetised plasma for both long nonlaminar warm relativistic driving beam (quantum-like domain of TWM) [3,4] and relatively cold relativistic quantum driving beam (quantum domain) [5,6]. Similarly, the self-modulation of a relativistic charged-particle beam as thermal matter wave envelope and the possibility of its destabilization was studied in [7] using the quantum-like description provided by the TWM in which the beam dynamics is governed by a Zakharov-type system of equations, comprising a Poissonlike equation for the wake potential and a nonlinear Schrödinger equation governing the spatiotemporal evolution of the thermal matter wave envelope, whose dispersion coefficient is proportional to the beam thermal emittance.…”
mentioning
confidence: 99%
“…Therefore, the pair of FSEs has been extended to a spinorial form (Fedele et al 2012a,b;Jovanovic et al 2012). In this way, a quantum approach to relativistically charged particle beams, named the Quantum Wave Model (QWM) (Fedele et al 2013), has been proposed and applied to plasma lens for quantum beams (Tanjia et al 2013). In this approach, similar to TWM, the space charge effects (both capacitive and inductive) are taken into account within the Hartree's mean field approximation.…”
Section: Relevance Of Fedele-shukla Equations For the Electron Wave Omentioning
confidence: 99%
“…In the strictly nonlocal regime, very recent work [11] shows a preliminary investigation to conceive a plasma lens [1,14,15] in quantum regime as a possible application towards focusing of the beam. The analysis has been carried out in the aberration-less approximation.…”
Section: Quantum Plasma Lensmentioning
confidence: 99%
“…FIG.7. Left: Variation of σ as a function of z [in cm] inside the lens with the initial condition of σ(0) = σ0 and σ (0) = 0, as reported in[11]. For a lens of thickness l = 1 mm, it has been found that σ(l) = 9.91 µm and f = 5.55 cm.…”
mentioning
confidence: 99%